Rekonsiliasi Antara Tuntutan Komodifikasi dan Substansi Agama dalam Pendidikan Islam (AL JAMI: Jurnal Ilmiah Keagamaan, Pendidikan dan Dakwah, 2023)
This research aims to examine the concept of reconciliation between the demands of commodification and the substance of religion in Islamic education in the 21st century. In the midst of efforts to provide quality Islamic education services, there is an impact on budgetary needs, including support from the user community, often creating the stigma of the 'commodification' of Islamic education. Meanwhile, the paradigm of Islamic education demands humanistic, religious, and sacred values, which are considered contrary to the commodification and capitalization approach in education. This research employs a literature review method, analyzing scholarly articles from journals and books related to the research theme. The results indicate a new paradigm in Islamic education that calls for the commodification process, yet Islamic education also seeks to engage in a dialogue with the sources of Islamic teachings, as well as the demands and needs of the time. The study emphasizes that religious values play a crucial role as a cohesive force in achieving students' peace while meeting the demands of the time. Therefore, a wise reconciliation between the demands of commodification and the substance of religion is paradigmatically needed in the context of modern Islamic educationKeywords: Reconciliation; Commodification ; Islamic Education  AbstrakPenelitian ini bertujuan untuk mengkaji konsep rekonsiliasi antara tuntutan komodifikasi dan substansi agama dalam pendidikan Islam pada abad ke-21. Di tengah upaya menyediakan layanan pendidikan Islam berkualitas, muncul dampak terhadap kebutuhan anggaran, termasuk dukungan dari masyarakat pengguna, yang seringkali menciptakan stigma 'komodifikasi' pendidikan Islam. Sementara itu, paradigma pendidikan Islam menuntut nilai-nilai humanis, agama, dan suci, yang dianggap bertentangan dengan pendekatan komodifikasi dan kapitalisasi pendidikan. Penelitian ini menggunakan metode tinjauan literatur dengan menganalisis artikel ilmiah dari jurnal dan buku yang terkait dengan tema penelitian. Hasil penelitian menunjukkan bahwa terdapat paradigma baru dalam pendidikan Islam yang menuntut proses komodifikasi, namun pendidikan Islam juga berusaha berdialog dengan sumber ajaran Islam serta tuntutan dan kebutuhan zaman. Penelitian ini menggarisbawahi bahwa nilai-nilai agama memainkan peran penting sebagai perekat dalam mencapai kedamaian siswa seiring dengan memenuhi tuntutan zaman. Oleh karena itu, secara paradigmatik diperlukan rekonsiliasi yang bijak antara tuntutan komodifikasi dan substansi agama dalam konteks pendidikan Islam modern.Kata kunci: Rekonsiliasi; Komodifikasi; Pendidikan Islam